2015
DOI: 10.1016/j.psyneuen.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, eudaimonia, and the human conserved transcriptional response to adversity

Abstract: Background Chronic social adversity activates a conserved transcriptional response to adversity (CTRA) marked by increased expression of pro-inflammatory genes and decreased expression of antiviral- and antibody-related genes. Recent findings suggest that some psychological resilience factors may help buffer CTRA activation, but the relative impact of resilience and adversity factors remains poorly understood. Here we examined the relative strength of CTRA association for the two best-established psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
144
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 78 publications
12
144
0
2
Order By: Relevance
“…The leukocyte CTRA represents one molecular process that may potentially mediate the health effects of negative psychological processes and adverse social conditions (Cole et al, 2007(Cole et al, , 2011(Cole et al, , 2015a(Cole et al, , 2015b. Little is known about how positive psychological processes may impact the CTRA, although several studies have found down-regulation of the CTRA in people with high levels of eudaimonic well-being (a multi-faceted complex of self-transcendent aspects of well-being, including purpose in life, positive relations with others, and several other prosocial components; Cole et al, 2015b;Fredrickson et al 2013Fredrickson et al , 2015Kitayama et al 2016).…”
Section: Human Social Genomicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The leukocyte CTRA represents one molecular process that may potentially mediate the health effects of negative psychological processes and adverse social conditions (Cole et al, 2007(Cole et al, , 2011(Cole et al, , 2015a(Cole et al, , 2015b. Little is known about how positive psychological processes may impact the CTRA, although several studies have found down-regulation of the CTRA in people with high levels of eudaimonic well-being (a multi-faceted complex of self-transcendent aspects of well-being, including purpose in life, positive relations with others, and several other prosocial components; Cole et al, 2015b;Fredrickson et al 2013Fredrickson et al , 2015Kitayama et al 2016).…”
Section: Human Social Genomicsmentioning
confidence: 99%
“…Little is known about how positive psychological processes may impact the CTRA, although several studies have found down-regulation of the CTRA in people with high levels of eudaimonic well-being (a multi-faceted complex of self-transcendent aspects of well-being, including purpose in life, positive relations with others, and several other prosocial components; Cole et al, 2015b;Fredrickson et al 2013Fredrickson et al , 2015Kitayama et al 2016). However, all of the results involving eudaimonic well-being come from cross-sectional studies, and it remains unclear whether there is any causal effect of eudaimonic well-being on CTRA gene expression or whether any such effects stem specifically from the prosocial components of eudaimonia.…”
Section: Human Social Genomicsmentioning
confidence: 99%
See 3 more Smart Citations